Interaction between Microsatellite Instability (MSI) and Tumor DNA Methylation in the Pathogenesis of Colorectal Carcinoma - Farzana Jasmine; Zahidul Haq; Mohammed Kamal; Maruf Raza; Gustavo da Silva; Katrina Gorospe; Rupash Paul; Patrick Strzempek; Habibul Ahsan; Muhammad G Kibriya (Cancers, 2021)
In colorectal cancer (CRC), the role of microsatellite instability (MSI) is well known. In a genome-wide scale, for the first time, we explored whether differential methylation is associated with MSI. We analyzed 250 paired samples from 125 CRC patients (m = 72, f = 53) at different stages. Of them, 101 had left-sided CRC, 30 had MSI, 34 had somatic mutation in KRAS proto-oncogene ( KRAS ), and 6 had B-Raf proto-oncogene ( BRAF ) exon 15p.V600E mutation. MSI was more frequent in right-sided tumors (54% vs. 17%, p = 0.003). Among the microsatellite stable (MSS) CRC, a paired comparison revealed 1641 differentially methylated loci (DML) covering 686 genes at FDR 0.001 with delta beta ≥ 20%. Similar analysis in MSI revealed 6209 DML covering 2316 genes. ANOVA model including interaction (Tumor*MSI) revealed 23,322 loci, where the delta beta was different among MSI and MSS patients. Our study shows an association between MSI and tumor DNA methylation in the pathogenesis of CRC. Given the interaction seen in this study, it may be worth considering the MSI status while looking for methylation markers in CRC. The study also indicates an opportunity for potential use of certain immune checkpoint inhibitors ( CTLA4 and HAVCR2 inhibitors) in CRC with MSI.